1970
DOI: 10.1111/j.1365-2818.1970.tb02242.x
|View full text |Cite
|
Sign up to set email alerts
|

Polarized light and phase‐contrast studies of stained and unstained plant cell nucleoli

Abstract: Nucleolar morphology in interphase nuclei of non-growing and growing plant cells has been studied by polarized light and phase-contrast microscopy. Variation in the optical properties of the nucleoli in unstained preparations are indicative of different morphological stages of this cell organelle with respect to the physiological status of the cells in which these variations occur. A filamentous nucleolar component, the nucleolonema, was evident in unstained nucleoli of explants cultured in vitro and in hypoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1971
1971
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…They demonstrated that tissue preparation steps such as deparaffinization, hydration and dehydration were important for nuclear birefringence. IBI has also been noted in lemon fruit explant cells cultured in vitro and imaged using polarized light and phase-contrast, but the signal was thought to depend on a filamentous nucleolar component 3 . Other studies have linked nuclear birefringence with lymphocyte activation in rat spleen cell suspensions stained with neutral red 4 and with liquid crystalline chromosome formations noted in dinoflagellate cultures 5 .…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated that tissue preparation steps such as deparaffinization, hydration and dehydration were important for nuclear birefringence. IBI has also been noted in lemon fruit explant cells cultured in vitro and imaged using polarized light and phase-contrast, but the signal was thought to depend on a filamentous nucleolar component 3 . Other studies have linked nuclear birefringence with lymphocyte activation in rat spleen cell suspensions stained with neutral red 4 and with liquid crystalline chromosome formations noted in dinoflagellate cultures 5 .…”
Section: Introductionmentioning
confidence: 99%